2019
DOI: 10.1002/ange.201906245
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Control of the Kinetic Propylene/Propane Separation by Zeolitic Imidazolate Framework‐8

Abstract: One intriguing feature of many porous MOFs is their stimulus-induced flexibility,w hichm akes them unique compared to standarda dsorbents.H ere we propose an innovative concept to achieve an efficient kinetic separation of species with similar properties by the mechanical fine-tuning of the pore architecture of the flexible zeolitic imidazolate framework ZIF-8. This unprecedented approach was applied to one of the most challenging societally relevant separations: the separation of propylene and propane,w hich … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Han et al considered point defects in ZIF-8 and found that linker vacancies and dangling linkers can increase hopping rates, so that the effect of these defects must be considered [234]. A recent study by Zheng and Maurin [235] on propane/propylene kinetic separations in ZIF-8 used high temperatures to simulate diffusion coefficients and extrapolated down to standard conditions using an Arrhenius plot; these results also compared well to the measurements by Chmelik et al [233] Zheng and Maurin showed that mechanical pressure exerted on ZIF-8 could improve propane/propylene separations by reducing the window size and significantly decreasing propylene diffusion relative to propane.…”
Section: Flexible Microporous Metal-organic Frameworkmentioning
confidence: 99%
“…Han et al considered point defects in ZIF-8 and found that linker vacancies and dangling linkers can increase hopping rates, so that the effect of these defects must be considered [234]. A recent study by Zheng and Maurin [235] on propane/propylene kinetic separations in ZIF-8 used high temperatures to simulate diffusion coefficients and extrapolated down to standard conditions using an Arrhenius plot; these results also compared well to the measurements by Chmelik et al [233] Zheng and Maurin showed that mechanical pressure exerted on ZIF-8 could improve propane/propylene separations by reducing the window size and significantly decreasing propylene diffusion relative to propane.…”
Section: Flexible Microporous Metal-organic Frameworkmentioning
confidence: 99%
“…The high integrity of the monolithic MOF film endows the nanoarchitecture with high mechanical strength, which was critical for their applications. [40][41][42][43][44][45][46][47][48][49] The force−displacement curves from nanoindentation test revealed that the hardness of the sample increased along with the pulse energy density impact on MOF layer (Figure 4B), reflected by a larger slope of the loading force curve which was associated to the higher relative hardness. The calculated hardness and Young's modulus of the structure all increased gradually with the laser energy density (Figure S12, Supporting Information), implying that more dense structure was formed under higher pressure.…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, separation based on physical adsorption has always been regarded as a promising gas separation technology owing to its advantages including simple operation, economic, and energy-efficient. Nevertheless, the practicality of the adsorptive separation and its efficiency is strongly based on the pore aperture and pore chemistry of the adsorbent employed. , Metal–organic frameworks (MOFs), a series of emerging porous materials, are constructed by metal node and multifunctional organic linkers. Because of their stable framework, adjustable pore size, and high surface area, MOFs have been investigated extensively in the gas separation field over the past several decades. Hitherto, considerable achievements were reported previously on the aspects of separating C 2 H 2 /C 2 H 4 , C 2 H 4 /C 2 H 6 , C 3 H 6 /C 3 H 8 , , CO 2 /C 2 H 2 , CO 2 /CH 4 /N 2 , and Xe/Kr. …”
Section: Introductionmentioning
confidence: 99%